Plasmodium falciparum pre-erythrocytic stage vaccine development (2020)
Worldwide strategies between 2010 and 2017 aimed at controlling malarial parasites (mainly Plasmodium falciparum) led to a reduction of just 18% regarding disease incidence rates. Many biologically-derived anti-malarial vaccine candidates have been developed to date; this has involved using many experimental animals, an immense amount of work and the investment of millions of dollars. This review provides an overview of the current state and the main results of clinical trials for sporozoite-targeting vaccines (i.e. the parasite stage infecting the liver) carried out by research groups in areas having variable malaria transmission rates. However, none has led to promising results regarding the effective control of the disease, thereby making it necessary to complement such efforts at finding/introducing new vaccine candidates by adopting a multi-epitope, multi-stage approach, based on minimal subunits of the main sporozoite proteins involved in the invasion of the liver. © 2020 The Author(s).